Pengaruh Gaya Kepemimpinan, Disiplin Kerja dan Motivasi Terhadap Kinerja Pegawai Kecamatan Sragen, Kabupaten Sragen - Andhika Rifaldhi Darmawan; Riska Fii Ahsani (Teewan Journal Solutions, 2026)
Employee performance is a crucial factor in determining the effectiveness of an organization, especially in the government sector, which is responsible for providing public services. Various factors, such as leadership style, work discipline, and motivation, play a significant role in enhancing or diminishing employee productivity within an institution. The purpose of this study is to analyze the influence of style, work discipline and motivation on the performance of employees in Sragen District. This research is a survey research on employees of Sragen District, Central Java. The determination of saturated sampling is carried out because the sample of the object being studied or the data source is small (less than 100 people). The data collection technique in this study is a questionnaire. The Research Instrument Test consists of a validity test and a reliability test. The classical assumption test consists of multicollinearity test, autocorrelation test, heteroscedasticity, normality test and multiple linear regression analysis. The hypothesis test consists of the t-test, the F-test (model accuracy test) and the determination coefficient (R2). Based on the results of research on employees of Sragen District, Central Java regarding the influence of leadership style, work discipline and motivation on the performance of employees of Sragen District, Central Java, the conclusion was obtained that the leadership style variable was not proven to be true, the work discipline variable was proven to be true and the motivation variable was proven to be true.